1997
DOI: 10.1080/00071669708418035
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between dietary fat type and xylanase supplementation when rye‐based diets are fed to broiler chickens 2. Performance, nutrient digestibility and the fat‐soluble vitamin status of livers

Abstract: 1. The interactions between dietary fat type and xylanase supplementation of rye-based diets were investigated using a 2 x 2 factorial design in which a rye-based diet (610 g rye/kg) was combined with 100 g/kg of soya oil or beef tallow, with or without xylanase supplementation at 3000 IU/kg, and fed to 1-d-old male broilers for 35 d. Growth, nutrient digestibility and AMEN values were determined and the vitamin status of livers assessed at various ages. 2. There were significant interactions between crude fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 37 publications
8
28
1
Order By: Relevance
“…The improvement in BWG of broilers that received TOM supplemented diets could be ascribed to increases in protein and energy retention. Dänicke et al (1997b) found that fat digestibility in broilers was improved by enzymes in two fat sources (soybean oil and beef tallow) but protein digestibility and AME N values were significantly improved by enzymes only in a tallow diet. It was reported that enzymes reduce the negative effects of NSPs and improve the digestion of nutrients in poultry diets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improvement in BWG of broilers that received TOM supplemented diets could be ascribed to increases in protein and energy retention. Dänicke et al (1997b) found that fat digestibility in broilers was improved by enzymes in two fat sources (soybean oil and beef tallow) but protein digestibility and AME N values were significantly improved by enzymes only in a tallow diet. It was reported that enzymes reduce the negative effects of NSPs and improve the digestion of nutrients in poultry diets.…”
Section: Discussionmentioning
confidence: 99%
“…Water-soluble NSPs fed to young chicks interfere with the digestion and absorption of other nutrients by increasing the viscosity of digesta in the gut (Ward & Marquardt, 1983). Xylanase supplementation was noted to increase the digestibility of insoluble pentosans (Dänicke et al, 1997b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that xylanase addition did not influence fat digestion suggests that viscosity was likely to be low. The effect of the xylanase on weight gain and particularly feed per gain was somewhat low compared with other studies where tallow and soy oil have been compared (Smulikowska and Mieczkowska, 1996;Danicke et al, 1997). A possible reason for this low response may lie in the use of mash diets, instead of pelleted diets.…”
Section: Discussionmentioning
confidence: 48%
“…Soybean oil is better utilised by poultry due to their high contents of unsaturated fatty acids, whereas tallow contains long chain saturated fatty acids, which are nonpolar and difficult to digest and absorb (Krogdahl, 1985). Some reports suggest that high concentrations of NSP in wheat influence the digestion and absorption of lipids in poultry, and that this effect is more evident when animal fats are used as the lipid source (Smulikowska and Mieczkowska, 1996;Danicke et al, 1997Danicke et al, , 1999aPreston et al, 2001). In the current work, therefore, the hypothesis that the influence of exogenous xylanase on bird performance and nutrient utilisation will be more pronounced in tallow-supplemented wheat-based diets compared to those supplemented with soybean oil was tested.…”
Section: Discussionmentioning
confidence: 99%